Posthuman counselling: understanding a counselling session as a materially entangled performative encounter - McFarlane, Audrey (The University of Edinburgh, 2023)
While counselling theory and practice has acknowledged the materiality of a counselling session, research into the entangled, dynamic relationship of the human and nonhuman in the counselling session remains largely unexplored. To date, counselling research has been predicated on assumptions that privilege the human over matter and which emphasize the binary positioning of the knower/known, subject/object, client and counsellor. This study looks to the feminist philosopher and quantum physicist Karen Barad whose theories encourage a fundamental rethinking of concepts which support this binary thinking and inspire a move towards an ethico-onto-epistemological view of counselling. This thesis is expanded by engaging with the work of Karen Barad to reconceptualize what we view as a counselling session in terms of an entangled performative encounter. It considers how the posthuman new materialist principles of agential realism might trouble our theorizing of a counselling session when viewed as a phenomena intra-actively co-constituted through the specific material discursive practices which emerge. The aim of the thesis is to demonstrate that when we emphasize the absolute indeterminacy of experience, acknowledging that past and future, the conscious and unconscious, are repeatedly reworked and enfolded through the iterative, dynamic practices of spacetimemattering a richer understanding of counselling experience begins to emerge. This thesis troubles the idea of defined prescriptive methodologies. It acknowledges instead that this thesis emerged iteratively and unpredictably and represents my attention to the agential enactments which emerged in the material-discursive practices of writing, thinking and reading my memories and experiences of counselling. It presents an exploration of what might emerge when we diffractively read, write and think the theories of psychodynamic theory through the posthuman new materialisms. It gives space to the differences and new understandings generated by an entangled reading of experience in counselling, a knowing in being. This thesis demonstrates that when we attend to the ethical and onto-epistemological matterings of the therapeutic encounter we produce a richer, more materially expansive understanding of counselling as an experience.
Keywords: Posthuman Counselling; agential realism; counselling; counselling session; Karen Barad; entangled performative encounter; psychodynamic theory; posthuman new materialisms